Attachment, Self-esteem, and Social Self-expression Skills: A Causal Chain Model in Young People and Adolescents - Homola, Sofía Yenien (2023)
Objectives. To analyze the relationship between attachment and self-esteem in young people and adolescents, and to examine the relationship between self-esteem and social self-expression skills, integrating these results into a causal chain model. Method. 387 adolescents and young people completed self-report scales. Regression analysis and structural equation modeling were performed. Results. Both secure and insecure attachment predicted participants’ self-esteem. Likewise, self-esteem was a predictor of social self-expression. The study concluded that the secure attachment established with the caregivers increases the possibility of developing a strengthened self-esteem, promoting the individual’s ability to express oneself socially. Conversely, insecure attachment weakens self-esteem, leading to impaired social self-expression.